Do attractive organisations fare better on the job market? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Some employers can come across as more alluring than others. Few job seekers, for instance, would ignore openings at Apple, Google, Nike or Goldman Sachs. And if they do, it may have more to do with their own self-esteem than a lack of wanting to work at some of these 'World's Most Admired Companies' (according to Fortune magazine's yearly list). However, why do some organisations seem more attractive than others, and does it factor into our own career decisions? Also, while it may seem as if attractive organisations will get their pick of the most desirable 'suitors', a new study shows that job seekers may not necessarily accept a job at organisations that they are attracted to.